(-96)×(-12)+(-28)=(-96)×(-12)+(-96)+(-28)

Question

(-96)×(-12)+(-28)=(-96)×(-12)+(-96)+(-28)

in progress 0
Caroline 1 month 2021-08-13T17:41:38+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-08-13T17:43:27+00:00

    \huge\boxed{\underline{\underline{\green{\tt Solution}}}}

    (-96)× \{(-12)+(-28) \}=(-96)×(-12)+(-96)+(-28)

    This property is called DISTRIBUTIVE PROPERTY

    \displaystyle\textcolor{red}{Please \:  Mark \:  it  \: Brainliest}

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )